Pendidikan Kesehatan Tentang Teknik Menyusui Yang Benar Pada Ibu Dengan Bayi Usia 0-6 Bulan Di Desa Getas Kec. Cepu, Kab. Blora - Amelia Nur Hidayanti (LPPM AN Nuur, 2021)
Background: The presence of a baby in a family is everyone's dream. Of course, a baby still has a high dependence on both parents. A mother is strongly recommended to give breast milk (Mother's Milk) as the main source of food before they are allowed to get other food sources. Mothers must pay attention to nutrition and have sufficient knowledge about how to care for a baby and how to breastfeed a baby properly and correctly. So that their babies can grow well and healthy. Purpose: The purpose of this service activity is to provide breastfeeding mothers with information on how to breastfeed properly. Method: The activity starts from counseling and is developed in the form of questions and practices. Results: input on the target 75% who attended from 30 invitees attended 12 people, the media was sufficient by using leaflets and the lecture method, the process of active participant activity as many as 8 mothers asked questions, the delivery of the material was clear and complete. The output on the question of understanding breastfeeding, participants answered correctly, the question of the benefits of breastfeeding, participants could answer quite completely, demonstrated the correct breastfeeding technique, participants could demonstrate it correctly. Conclusion: By conducting community service programs in the form of Health Education and Training on Correct Breastfeeding Techniques in Getas Village, as a community service effort to increase knowledge of breastfeeding mothers about correct breastfeeding techniques so that breastfeeding mothers realize how important correct breastfeeding techniques are so that babies can breastfeed comfortably, and the mother's nipples are not sore.K